Sarcoidosis in a patient presenting with clinical and histological features of primary Sjögren's syndrome. - Melsom, R D (1988)
A patient presenting with bilateral enlargement of parotid and lacrimal glands, xerostomia, and keratoconjunctiva sicca, whose labial biopsy specimen showed changes consistent with Sjögren's syndrome, is described. The patient was initially misdiagnosed as having primary Sjögren's syndrome (SS). Subsequent investigations, however, performed to exclude an associated lymphoma or sarcoidosis, showed histological changes of the latter. The possibility that early infiltrates of the salivary glands in sarcoid may mimic those of SS is discussed.